Professional Noticing in Entrepreneurship Education : Towards an Entrepreneurial Mindset in Higher Education - Ahokas, Ira; Grundschober, Isabell; Grönlund, Mikko; Carty, Anthony; Finkel, Lucila; López-Varela, Asunción; Krüger, Aisha; Alonso, David; Fernández, Carolina; Parra, Pilar; Cassina, Luna (Finland, 2026)
This study explores the integration of Professional Noticing (PN) into entrepreneurship education to foster entrepreneurial mindset in higher education. PN is defined as the ability to observe, interpret, and respond to salient information in professional contexts. Despite its potential, PN has remained underused in entrepreneurship education pedagogy. The research, conducted under the EU-funded PROMISE project, involved 15 pilot trainings across Austria, Finland, Spain, and Ireland. A mixed-methods approach was employed, including a student survey (n=183) and 15 semi-structured teacher interviews.
Findings indicate that PN enhances key entrepreneurial competences such as creativity, selfawareness, and opportunity recognition. Students reported moderate to significant improvements in their entrepreneurial competences. Factor analysis revealed six competence clusters, with the strongest loading in Factor 1, which showed the most significant transformation following the pilot training. All entrepreneurial competences and all four PN skills were strongly represented and showed high loadings.
Teacher interviews showed that PN supports a broad range of entrepreneurial competences, particularly opportunity recognition, creativity, reflective judgment, and risk management. Teachers highlighted PN’s value in structuring learning, promoting learner-centred pedagogy, and bridging theory with practice.
The study concludes that PN is a promising pedagogical tool for entrepreneurship education, supporting the development of transversal skills essential in dynamic work environments.
Muutosten tekijät yrittäjyyskasvatuksessa YKTS Yrittäjyyskasvatuspäivät 2025 – Konferenssijulkaisu = Changemakers in Entrepreneurship Education YKTS Entrepreneurship Education Conference 2025 – Conference Proceedings